Tobacco production in the Eastern Province of Zambia - Whittington, G. (ERDKUNDE, 1967)
In the area around Fort Jameson, located in eastern Zambia and settled by Europeans, flue-cured Virginia tobacco became the most important cash crop after 1910. From 1910-1928 production increased to 1.35 million kg; from 1929-1937 prices fell and many plantations were abandoned and deserted. From 1938-1946 the war caused an increase in production: the harvest amounted to 0.9 million kg per year. Economic conditions were favorable from 1947-1953; new settlers created new plantations and production increased to 2 million kg. Since 1953 the plantations have been abandoned again. As the European settlers emigrated from this area, the production of Virginia tobacco came to an almost complete standstill. This collapse resulted from the marketing and transport difficulties and the inadequate management. The land left by the Europeans (called Crown Land) is now being prepared for African tillage. It is interesting that in one of the areas attempts are being made to set up individual farms (system of individual tenure).